2002
DOI: 10.1046/j.1439-0507.2002.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports. Isolation of two Trichosporon cutaneum strains from urine

Abstract: Two strains of Trichopsoron cutaneum were isolated from the urine of two male patients. Antifungal susceptibility and cross-reactivity with Cryptococcus antigen latex agglutination text as well as the patients' situation are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In the present investigation the pathogenic role of such variety of compounds, collectively included in the yeast culture filtrate, (especially those of C.albicans, C. glabrata and C. tropicallis) was confirmed with an obvious effects on the viability, and induction appearance of various clinical symptoms ending with mortalities accompanied with destructive changes in the livers, kidney and spleen of the intravenously injected mice. The reports dealing with the pathogenic role of yeasts 2 ry metabolites are scanty, however our findings support these reports [35,36].…”
Section: Discussionsupporting
confidence: 86%
“…In the present investigation the pathogenic role of such variety of compounds, collectively included in the yeast culture filtrate, (especially those of C.albicans, C. glabrata and C. tropicallis) was confirmed with an obvious effects on the viability, and induction appearance of various clinical symptoms ending with mortalities accompanied with destructive changes in the livers, kidney and spleen of the intravenously injected mice. The reports dealing with the pathogenic role of yeasts 2 ry metabolites are scanty, however our findings support these reports [35,36].…”
Section: Discussionsupporting
confidence: 86%
“…Karigane et al reported Trichosporon asahii fungemia in an AML patient with positive cryptococcal antigenemia 5 days before the isolation of the fungus [ 25 ], while others reported a positive cryptococcal antigen concomitantly [ 16 ] or after the yeast isolation [ 20 , 26 ]. Interestingly, in our patient, the cryptococcal antigen was positive in several biological fluids, such as urine or cerebrospinal fluid, all confirmed by a subsequent Trichosporon positive culture [ 19 , 22 ].…”
Section: Discussionmentioning
confidence: 77%
“…are Basidiomycota, and cross-reactions between cryptococcal polysaccharide antigen detection and Trichosporon species are known [ 16 , 17 ]. Until now, the reported cases of cross-reactions concerned the following species: Trichosporon cutaneum [ 18 , 19 ], Trichosporon beigelii [ 16 , 20 , 21 , 22 , 23 ], Trichosporon asahii [ 24 , 25 ] and Trichosporon dermatis [ 26 ]. We present the first case of a positive cryptococcal antigen detection during a Trichosporon japonicum infection.…”
Section: Discussionmentioning
confidence: 99%
“…Trichosporon has been associated with urinary tract abnormalities or catheters, but does not typically lead to systemic disease [23,24]. Urinary tract disease due to Cryptococcus neoformans, in contrast, is usually secondary to systemic infection, particularly in immunocompromised patients [25][26][27][28].…”
Section: Epidemiologymentioning
confidence: 99%